2020
DOI: 10.1002/jcla.23251
|View full text |Cite
|
Sign up to set email alerts
|

ALKBH5 gene polymorphisms and Wilms tumor risk in Chinese children: A five‐center case‐control study

Abstract: Background: Wilms tumor is a frequently diagnosed renal cancer among children with unclear genetic causes. N6-methyladenosine (m 6 A) modification genes play critical roles in tumorigenesis. However, whether genetic variations of m 6 A modification genes predispose to Wilms tumor remain unclear. ALKBH5 (AlkB homolog 5), a crucial member of m 6 A modification genes, encodes a demethylase that functions to reverse m 6 A RNA methylation. Methods: Herein, we evaluated the association of single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…N6‐methyladenosine (m 6 A), the most abundant and prevalent modification of mRNAs, has been demonstrated to significantly associate with gene expression 18 . An increasing number of m 6 A‐related cancers have been verified in recent years, including leukemia, 19 glioblastoma, 20 Wilms tumor, 21 bladder cancer, 22 endometrial cancer 23 and colorectal cancer 24 . M 6 A‐associated enzymes play a synergistic or opposite role in cancer progression 25 .…”
Section: Introductionmentioning
confidence: 99%
“…N6‐methyladenosine (m 6 A), the most abundant and prevalent modification of mRNAs, has been demonstrated to significantly associate with gene expression 18 . An increasing number of m 6 A‐related cancers have been verified in recent years, including leukemia, 19 glioblastoma, 20 Wilms tumor, 21 bladder cancer, 22 endometrial cancer 23 and colorectal cancer 24 . M 6 A‐associated enzymes play a synergistic or opposite role in cancer progression 25 .…”
Section: Introductionmentioning
confidence: 99%
“…For further mechanistic insight, we analyzed m6A-modifying enzymes in Wilms' tumor. Ao Lin et al has recently demonstrated that polymorphisms of the m6A methylase METTL3 are related with Wilms tumor susceptibility in Chinese children [23], and Rui-Xi Hua et al's work suggests that SNPs in the m6A demethylase ALKBH5 may exert a weak in uence on susceptibility to Wilms' tumor [24]. These studies analyzed only the possible relation between the WT and m6A "writers" and "erasers", though effects on "readers" in Wilms' tumor remained undetermined prior to our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 414 patients and 1199 controls were enrolled from five regions in China, 31–33 for which the demographic characteristics and selection criteria have been described in detail in previous studies 34,35 . Briefly, patients were diagnosed with Wilms tumor based on the results of imaging and histopathological examinations, and the controls were healthy children whose age and sex were effectively matched to the patients (see Supporting information, Table S1).…”
Section: Methodsmentioning
confidence: 99%